Ionic Liquid as a Green Media for the One-Pot Synthesis of New α- Thiazolodepsipeptide Derivatives via a Four-Component Reaction - S. Shahvelayati, Ashraf; Ashouri, Akram; S. Delbari, Akram (Letters in Organic Chemistry, 2016)
Background: A depsipeptide is a molecule that has both peptide and ester linkages in proximity in the same amino acid-containing small molecule or chain. Many depsipeptides show very promising biological activities, including anticancer, antibacterial, anticancer, antiviral, antifungal, anti-inflammatory, and anti-clotting or anti-antherogenic properties. The aim of this paper is to apply ionic liquid as a green media for the synthesis of new α-thiazolodepsipeptide derivatives via a four-component reaction. Methods: Thiazole-containing depsipeptides were produced easily in one step by a four-component Condensation/ Passerini tandem reaction of thiourea carboxylic acid derivatives, phenacyl bromides, ketones and isocyanides in 1-methyl-3- pentylimidazolium bromide as new solvent. Results: As shown in Scheme 1, the reaction of thiourea carboxylic acid 1, phenacyl bromide or its derivatives 2, alkyl isocyanides 3 and ketones 4 in an ionic liquid at 50°C produce depsipeptide derivatives 5 in good yield. The products were characterized by 1H NMR, 13C NMR, Mass ,and IR spectroscopy. This reaction carried out based on combination of cyclization and passerini reactions. Conclusion: In summary the reaction of thiourea carboxylic acid, phenacyl bromide or its derivatives, alkyl isocyanides and ketones in ionic liquid at 50°C produce depsipeptide derivatives in good yields. The advantage of the present procedure is that all four substrates were mixed in ionic liquid as a one-pot reaction without any catalyst and without the need for separation of intermediates.
Keywords: passerini reaction